Pediatric Solid Gastric Emptying Scintigraphy: Normative Value Guidelines and Nonstandard Meal Alternatives. (19th November 2020) - Ng, Thomas S.C.; Putta, Niharika; Kwatra, Neha S.; Drubach, Laura A.; Rosen, Rachel; Fahey, Frederic H.; Flores, Alejandro; Nurko, Samuel; Voss, Stephan D.
Abstract : INTRODUCTION: Adult standards for gastric emptying scintigraphy, including the type of meal and range of normative values for percent gastric emptying, are routinely used in pediatric practice, but to date have not been validated. The purpose of this study is to determine whether the use of adult criteria for gastric emptying scintigraphy is valid for children and whether alternative nonstandard meals can also be offered based on these criteria. METHODS: This retrospective study analyzed patients (n = 1, 151 total) who underwent solid-phase gastric emptying scintigraphy. Patients were stratified into normal and delayed gastric emptying cohorts based on adult criteria, i.e., with normal gastric emptying defined as ≤10% gastric retention at 4 hours. Patients were further stratified based on the type of meal, namely complete or partial adult standard meals or alternative cheese-based meals. Percent gastric retention values at 1, 2, 3, and 4 hours were compared. RESULTS: The median (95% upper reference limit) percentage gastric retention values for the complete standard meal were 72% (93%) at 1 hour, 39% (65%) at 2 hours, 15% (33%) at 3 hours, and 6% (10 %) at 4 hours. By comparison, the values for cheese-based meals were 60% (87%) at 1 hour, 29% (61%) at 2 hours, 10% (30%) at 3 hours, and 5% (10%) at 4 hours. Consumption of at least 50% of the standard meal yielded similar retention percentages; 68% (89%) at 1 hour, 32% (57%) at 2 hours, 10% (29%) at 3 hours, and 5% (10%) at 4 hours. There were no significant age- or sex-specific differences using the adult criteria. DISCUSSION: The adult normative standards for gastric emptying scintigraphy are applicable for use in the pediatric population. These same standards can be also be applied to nonstandard meal options, including cheese-based alternative meals and partial standard meals.